Development of diagnostic tools and discovery of two novel Indian citrus ringspot virus species: insights into global mandarivirus phylogeography - Bharsakale, Rushikesh D.; Gubyad, Mrugendra G.; Mukherjee, Krishanu; Kokane, Amol D.; Kokane, Sunil B.; Misra, Pragati; Ghosh, Dilip Kumar (Frontiers in Microbiology, 2025)
Emerging viral pathogens, Indian citrus ringspot virus (ICRSV) and Citrus yellow vein clearing virus (CYVCV), pose significant threats to global citrus production, a cornerstone of agriculture and trade. The rapid transboundary spread of CYVCV underscores the urgent need for effective diagnostic tools. To tackle this issue, we developed a novel RT-PCR assay capable of simultaneously detecting ICRSV and CYVCV with high sensitivity and specificity in a single reaction. This assay, targeting conserved genomic regions, provides a cost-effective, reliable, and scalable diagnostic solution. Field validation across 49 citrus samples revealed infection rates of 61.22% for ICRSV and 24.48% for CYVCV, with notable co-infections, highlighting its precision and utility. Phylogenetic analyses uncovered substantial genetic diversity, delineating two ICRSV species (ICRSV-A and ICRSV-B) and eight geographically clustered CYVCV clades, reflecting trade-driven and environmental dispersal patterns. These findings emphasize the need for region-specific diagnostics and tailored management strategies. By addressing critical diagnostic gaps, this assay enables early detection and intervention, reducing economic losses and enhancing efforts to control emerging citrus pathogens. Additionally, it provides a foundation for future epidemiological research and contributes to the sustainability of global citrus production.